PENERIMAAN KELUARGA TERHADAP ANGGOTA KELUARGA YANG MENDERITA SKIZOFRENIA: Family Self-Acceptance in Schizophrenic Patients - Kurnia Citra Puspita; Mira Wati (unprimdn.ac.id, 2022)
Mental disorders should get more attention because the people themselves still think that mental disorders are disgusting and embarrassing. For this reason, the stigma of society has an impact on the families of sufferers because they think that if one of the families suffers from a mental disorder, it is something that is very embarrassing and is a disgrace to the family. One of the many psychiatric disorders is schizophrenia where the sufferer has difficulty distinguishing what is real and what is not. The existence of this thinking disorder makes the sufferer have abnormalities in behaving and speaking. Families who care for people with schizophrenia also receive bad treatment by the surrounding environment so that it affects their perception of schizophrenia itself. Not infrequently the family also becomes a victim when caring for the patient and of course makes the sufferer's family feel depressed. For this reason, self-acceptance from the family will have an impact and can also help the healing process for people with schizophrenia. The stages of family self-acceptance vary, but in general there are four stages, namely resistance, anger, bargaining, depression and acceptance.